Penerapan Decision Tree Data Mining Pada Produksi Kelapa Sawit PT Hindoli Di Sungai Lilin Kabupaten Musi Banyuasin - Atika Kurnia; Ahmad Haidar Mirza; Andri Andri (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
Data mining is an interesting pattern extraction of large amounts of data. PT Hindoli itself has a decision support information system that applies the c4.5 data mining algorithm. Given the large amount of data available, data mining estimates that palm oil production for a month is from production data. As one of the companies engaged in processing palm oil and producing palm oil, palm oil, and high-quality seed oil, which are grown by farmers into materials that can be sold and will be distributed to production data. The method used is the decision tree method to explore data, find hidden relationships between a number of prospective variables, among others, the number of producing oil palm based on the year, production, competition, and price, resulting in data accumulation or data grouping every month. Input with the target variable is expected to help PT Hindoli in monitoring palm oil processing.